Avoiding cord extraction or mobilization during pediatric inguinal hernia repair: a step midway between conventional and minimally invasive approaches. Issue 3 (July 2016) - Khirallah, Mohammad G.; Daowood, Hamada; Ali, Abdelfatah; Ashour, Mhamed
Abstract : Background: Pediatric inguinal hernia (PIH) represents one of the most common congenital defects in infants and children worldwide. Several techniques have been adopted for repair. Conventional open excision of the sac is considered the most popular and most accepted among pediatric surgeons. In the past few years laparoscopic PIH repair has started to gain popularity. Aim: The aim of this study was to minimize the intervention to be near to minimally invasive but at the same time to be conventional in approach, reducing the stretch and manipulation of the vital cord structures. Patients and methods: During the period from April 2013 to May 2015, 200 male infants who presented with PIH were operated upon in our hospital. We excluded patients with complicated inguinal hernias, hernias associated with hydroceles, undescended testis, and female infants. Results: Of the 200 male infants with PIH who were operated upon, 107 had hernias on the right side, 74 had on the left side, and 19 were bilateral. The mean age was 4.5 months. The mean body weight was 5 kg. All infants received general anesthesia. The mean length of the incision was 10 mm. Recurrence was found in only three cases. There were no cases of testicular atrophy. Conclusion: We found our approach to be safe and easy to perform, and the vital structures in the cord did not have to be manipulated.